Relationship between carbon source, production and pattern action of α-amilase from Rhizopus sp - Cruz, Rubens [UNESP]; De Souza, Elisângela Lúcio [UNESP]; Hoffmann, Erika Heilena Esther [UNESP]; Bellini, Marcia Zilioli [UNESP]; Cruz, Vinícius D'Arcadia [UNESP]; Vieíra, Claudia Roberta [UNESP] (My University, 1997)
This paper discusses the inducer effect of corn soluble starch and the individual components (amylose and amylopectin) from corn and potatoes starch for α-amylase production by a strain of Rhizopus sp. The following decreasing order in the enzyme production was obtained: corn amylose > potatoes amylose > corn amylopectin > potatoes amylopectin > starch > maltose, coinciding with the ability of the enzyme to release reducing units, except the soluble starch that was more softly hydrolysed. However, when the enzyme action was measured by the iodine binding method, an inverse order of enzyme activity was obtained, that is: amylopectins > starch > amylosis. The results suggest that: a) branched structures in substrate affect the enzyme production; b) corn amylose and corn amylopectin are better inducers than their respectives homologous from potatoes; c) α-amylase from Rhizopus sp has different action patterns on substrates with straight or branched chains: from the former, it removes only reducing units with lower molecular weight (G1-G3); from the latter it also removes oligosaccharides with higher molecular weight (G5-G6).
Keywords: α-amylase; Amylopectin; Amylose; Induction; Rhizopus sp; Starch